Marginal fit at cylinder-abutment interface before and after overcasting procedure Adaptação marginal na interface intermediário-cilindro antes e após as sobrefundições - Luciana Martins Cres Moraes; Paulo Henrique Orlato Rossetti; Leylha Maria Nunes Rossetti; Ana Paula Ribeiro do Vale Pedreira; Accacio Lins do Valle; Wellington Cardoso Bonachela (University of São Paulo, 2005)
The aim of this study was to measure marginal fit at cylinder-abutment interface, before and after overcasting procedure. A hexagonal implant was fixed to a stainless steel base and a Estheticone-like abutment used during all the experiment. Before casting procedure, gold (Group I) and Ni-Cr-Be (Group II) premachined cylinders were tightened to the abutment with gold and titanium screws (in both groups), with 10Ncm and 20Ncm torque values for the same screw type. Vertical measures were taken at the light microscope (Mitutoyo 5050, Tokyo, Japan) three times in six different parts along the abutment-cylinder interface for each torque value. Cylinders were overcast with Ag-Pd (Group I) or Ni-Cr-Be (Group II) alloy. After casting, the same measures and torque values were repeated. Intragroup differences (10 or 20Ncm torque values, before and after casting) and intergroup differences (10 and 20Ncm torque values, before or after casting) were analyzed by the Paired t Test; (p<0.05). Intragroup differences were observed for G-I (gold, 20Ncm, titanium screw, p=0.044) and for G-II (Ni-Cr-Be, 10Ncm, gold screw, p=0.002). Intergroup differences only were not observed in the G-II group (Ni-Cr-Be, 10 and 20Ncm, titanium screw, p=0.534). Within the limits of this study, the following conclusions can be drawn: 1) Regardless of screw type, marginal misfit was higher for Ni-Cr-Be cylinders after casting, but within acceptable levels of fit; 2) The combination of gold cylinders with gold or titanium screws was the most effective to reduce marginal misfit; 3) Both screw types did not improve marginal fit of Ni-Cr-Be cylinders after overcastting, and 4) Although a 20Ncm torque improved marginal fit in all situations, its use is not recommended due to the increased risk of prosthesis failure. Ni-Cr-Be alloys may be successfully used in single-tooth implant restorations, with no damage to the fit between abutment and prosthetic cylinder. O objetivo deste estudo foi medir a adaptação marginal na interface intermediário-cilindro, antes e após a sobrefundição. Um implante do tipo hexágono externo afixado numa base de aço inoxidável e um intermediário do tipo Estheticone foram usados durante todo o experimento. Antes das fundições, cilindros pré-usinados de ouro (Grupo I) e de Ni-Cr-Be (Grupo II) foram aparafusados ao intermediário com parafusos de ouro e titânio em ambos os grupos, com torques de 10Ncm e 20Ncm para o mesmo tipo de parafuso. As medidas verticais foram feitas num microscópio óptico (Mitutoyo 5050, Tóquio, Japão) três vezes em seis locais diferentes ao longo da interface intermediário-cilindro para cada valor de torque. Os cilindros foram encerados e fundidos tanto em liga de Ag-Pd (Grupo I) ou liga de Ni-Cr-Be (Grupo II). Após as fundições, as mesmas medidas e os mesmos valores de torque foram repetidos. As diferenças intra-grupo (torques de 10 ou 20Ncm, antes e após as fundições) e as diferenças inter-grupos (torques de 10 e 20Ncm, antes ou após as fundições) foram analisadas pelo teste t pareado (p<0.05). Diferenças intra-grupo foram observadas em G-I (ouro, 20Ncm, parafuso de titânio, p=0,044) e em G-II (Ni-Cr-Be, 10Ncm, parafuso de ouro, p=0,002). As diferenças inter-grupos não foram observadas somente no grupo G-II (Ni-Cr-Be, 10 e 20Ncm, parafuso de titânio, p=0,534). Dentro dos limites deste estudo, as seguintes conclusões podem ser feitas: 1) Independente do tipo de parafuso, os valores de desadaptação marginal foram mais altos para os cilindros de Ni-Cr-Be após as fundições, mas dentro dos níveis aceitáveis de adaptação; 2) A combinação cilindro de ouro com parafuso de ouro ou de titânio foi a mais efetiva para reduzir o desajuste marginal; 3) Ambos os tipos de parafusos não melhoraram a adaptação marginal dos cilindros de Ni-Cr-Be após as fundições, e 4) Embora um torque de 20Ncm tenha melhorado a adaptação marginal em todas as situações, seu uso não é recomendado devido ao risco aumentado de falha na prótese . As ligas de Ni-Cr-Be podem ser usadas com sucesso nas restaurações unitárias sobre implantes, sem prejuízo na adaptação entre o abutment e o cilindro protético.